A comparative cross-sectional study on the quality of life in Grave’s disease patients: urban vs. rural perspectives - Mishra, Shivang; Singh, Anurag Kumar; Rajotiya, Sumit; Debnath, Sourav; Kumar, Sachin; Singh, Pratima; Snehpreet,; Raj, Preeti; Singh, Mahaveer; Bareth, Hemant; Nathiya, Deepak; Singh Tomar, Balvir (Frontiers in Public Health, 2024)
Grave’s disease affects numerous patients globally, but its impact on health-related quality of life (HR-QoL) in relation to geographical disparities remains under-explored. This cross-sectional study aimed to assess the influence of urban versus rural residence on HR-QoL among patients diagnosed with Graves’ Disease in Rajasthan, India. One hundred seven Graves’ disease patients from rural and urban endocrine centers were analyzed. The rural group included 52 patients (24 males, 28 females), averaging 38.9 ± 10.9 years of age, while the urban group had 55 (13 males, 42 females) with an average age of 39.1 ± 14.2 years. We found differences between rural and urban patients in terms of gender ratio, BMI, smoking habits, and obesity. Multivariable linear regression was used in both groups to determine the association between the baseline characteristics of Graves’ patients from both areas and HR-QOL. Health-related quality of life, assessed via the SF-36 questionnaire, indicated higher general health and role emotional scores among urban patients. Our study found that the duration of Graves’ disease in rural centers negatively impacted physical health scores. In urban patients, age and BMI influenced physical health, while gender and disease duration affected mental health scores in rural patients. Age impacted mental health in urban patients. Rural patients had a poorer quality of life compared to urban patients. Differences in gender distribution, BMI, smoking habits, and obesity rates revealed disparities in Graves’ disease between rural and urban patients in India, highlighting the need for better healthcare infrastructure and awareness in rural areas.